A novel method for determining the time-temperature superposition relationship of SBS modified bitumen: Effects of bitumen source, modifier type and aging. (19th April 2021) - Chen, Zihao; Zhang, Henglong; Liu, Xinqi; Duan, Haihui
Highlights: Phase angle plateau region of SBSMBs is sorted into "convex" and "S" two shapes. The new method is useful for SBSMB with different bitumen sources and SBS types. The new method is not applicable to aged SBSMB samples. Abstract: The time-temperature superposition principle (TTSP) is frequently applied in rheological characterization of styrene-butadiene−styrene triblock copolymer (SBS) modified bitumen (SBSMB). The time-temperature superposition relationship is traditionally determined through optimizing the horizontal displacement of isothermal curves to minimize the errors between measured and predicted rheological data. Different from traditional method, the newly proposed method can determine the time-temperature superposition relationship of SBSMB according to its special points of phase angle plateau regions in isochronal curves. Nevertheless, the validity of this new method is only demonstrated for limited sources of SBSMB in previous study. In present paper, the effects of bitumen source, modifier type and aging on validity of the newly proposed method for determining the time-temperature superposition relationship of SBSMB were investigated. The results indicated that the shape of phase angle plateau region can be totally sorted into "convex" and "S" two types for all kinds of SBSMB samples. Although the rheological properties of SBSMB are affected by different bitumen sources and modifier types, the proposed method is demonstrated to be applicable to SBSMB samples prepared by different bitumen sources and modifier types. The proposed method cannot be applied to short-term or long-term aged SBSMB samples due to disappearance of phase angle plateau region. And the shift factors of original SBSMB obtained from the newly proposed method are no longer suitable for its aged SBSMB samples.